Babi Sebagai Media Ekspresi Kritik Sosial Dalam Penciptaan Seni Lukis - Darma Yoga, I Made; Setem, I Wayan; Murdana, I Ketut (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2021)
Pig is one of animal which has its own characteristics, both in terms of physical and characteristics that distinguish them from other animals. Pigs are greedy, dirty, lazy, stupid, savage, lustful and so on. By understanding to involve and observe a pig from their uniqueness on people's life, either directly or indirectly, it will lead to an understanding and perspective in assessing everything which is experienced in daily life. With the background of observing the life of pig in Balinese society in particular, the creator has an interest in expressing it into painting. The creation of this painting tries to visualize a metaphor from the characteristics of pig which is exist in the present context of human. It can be seen from the society phenomena which actually reflect the characteristic of the pig itself. In realizing ideas and themes in artworks through process, experiment, preparation, formation and finishing. Creating the artwork by organizing the elements and elements of art on a two dimension. Regarding the displayed theme, they are sourced from the nature environment and personal experience which is interesting or imprint in memory and provide memories so that the artwork will create as a record of personal life. Personally in this context, the creator sees various interesting things which can be expressed through the depiction of the characteristics of a pig, which can be concluded that with the life of a pig, the creator can understand, express, interpret the characteristic of a pig as a social critique in the creation of an artwork.